Mesozoic exhumation and tectonic evolution of the East Junggar region, NW China: Constraints from multi-system low-temperature thermochronology - Miao Han; Jiyuan Yin; Stuart N. Thomson; Yamei Wang; Fucheng Tan; Yunchuan Zeng; Zhiyuan He; Yuruo Shi; Tao Wang; Wenjiao Xiao (Journal of Asian Earth Sciences, 2026)

Multi-stage differential exhumation of the West Junggar and adjacent regions, NW China, revealed by regional low-temperature thermochronology - Yamei Wang; Jiyuan Yin; Wenjiao Xiao; Stuart N. Thomson; Tao Wang; Yannan Wang; Zhiyuan He; Wen Chen; Keda Cai; Fucheng Tan; Johan De Grave (Earth-Science Reviews, 2025)

Meso-Cenozoic Tectonic and Thermal History of the Kuqa Depression, Tarim Basin: Insights from Low-Temperature Thermochronology and Vitrinite Reflectance - Wenhao Xia; Jiyuan Yin; Zhiyuan He; Stuart N. Thomson; Fucheng Tan; Yamei Wang (Journal of Earth Science, 2025)

First cycle or polycyclic? Combining apatite and zircon detrital U-Pb geochronology and geochemistry to assess sediment recycling and effects of weathering - Emily S. Finzel; Stuart N. Thomson; David M. Pearson; L．Kenneth Horkley; Kacey Garber; Cole Gardner (Earth and Planetary Science Letters, 2025)

Meso—Cenozoic Exhumation of the Altai-Sayan Region: Constrained by Available Low-Temperature Thermochronology - Yamei Wang; Jiyuan Yin; Stuart N. Thomson; Wen Chen; Keda Cai; Zengchan Dong; Fucheng Tan (Journal of Earth Science, 2024)

Three-stage, 70 Myr exhumation of HP/LT rocks on Margarita, Venezuela: Caribbean intra-forearc shear, Grenada Basin rifting, and continental obduction - Walter V. Maresch; James Pindell; Rolf Kluge; Albrecht Baumann; Diego Villágomez Díaz; Manfred R. Brix; Stuart N. Thomson; Klaus Peter Stanek; Hans-Peter Schertl; Friedemann Grafe (Journal of South American Earth Sciences, 2024)

Neogene–Quaternary initiation of the Southern Malawi Rift and linkage to the reactivated Carboniferous–Jurassic Shire Rift - Oyewande Ojo; Stuart N. Thomson; Daniel A. Laó-Dávila (Tectonophysics, 2024)

Mesozoic exhumation of the northern West Junggar, NW China: Insights from low-temperature thermochronometers - Yamei Wang; Yannan Wang; Jiyuan Yin; Stuart N. Thomson; Wenjiao Xiao; Zhiyuan He; Wen Chen; Keda Cai; Mingxuan Wu; Yun Meng (Tectonophysics, 2023)

Corrigendum to “Thermal history of the Siberian Traps Large Igneous Province revealed by new thermochronology data from intrusions” [Tectonophysics 836 (2022) 229385] - Tatyana E. Bagdasaryan; Stuart N. Thomson; Anton V. Latyshev; Roman V. Veselovskiy; Victor A. Zaitsev; Alexander E. Marfin; Vladimir S. Zakharov; Denis S. Yudin (Tectonophysics, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The Žermanice sill: new insights into the mineralogy, petrology, age, and origin of the teschenite association rocks in the Western Carpathians, Czech Republic - Dalibor Matýsek; Jakub Jirásek; Petr Skupien; Stuart N. Thomson (International Journal of Earth Sciences, 2018)

The geodynamics of collision of a microplate (Chilenia) in Devonian times deduced by the pressure–temperature–time evolution within part of a collisional belt (Guarguaraz Complex, W-Argentina) - Arne P. Willner; Axel Gerdes; Hans-Joachim Massonne; Alexander Schmidt; Masafumi Sudo; Stuart N. Thomson; Graciela Vujovich (Contributions to Mineralogy and Petrology, 2011)